Organ specificity in the circadian control of plant gene expression. (26th October 2005) - Sullivan, S.; Shenton, M.; Nimmo, H.G.
Abstract : Of the many plant genes whose expressions are controlled by the circadian clock, one of the phosphoenolpyruvate carboxylase kinase genes in soya bean ( Glycine max ) exhibits the unusual property that its control is organ-specific – it is under circadian control in leaves but not in roots. Preliminary experiments suggest that the same is true for at least one gene in Arabidopsis thaliana . It will be important to define the extent and function of this phenomenon and the underlying mechanism.